72 State earned income tax credit policies and intimate partner homicide in the United States, 1990–2016. (5th May 2020) - Moe, Caitlin; Adhia, Avanti; Edmonds, Amy T; Mooney, Stephen J; Hill, Heather D; Rivara, Frederick P; Rowhani-Rahbar, Ali
Abstract : The Earned Income Tax Credit (EITC) is the largest cash transfer program to low-income working families in the U.S. Some states augment the federal EITC with variable levels of generosity. As lack of finances is the most frequently-cited barrier for women to leave abusive relationships, federal and state EITCs could provide financial means to leave abusive relationships. However, the financial control associated with abuse and current EITC eligibility rules may hinder the program's use for this purpose. We hypothesized that increased generosity in state EITC's would be associated with a reduction in intimate partner homicide (IPH). Approach: Using multiply-imputed Supplementary Homicide Reports, we obtained state- and year-level counts of female IPH victims aged 18 or older for 1990–2016. Using a difference-in-differences approach and linear regression with state- and year- fixed effects, we assessed the impact of changes in EITC generosity on annual rates of IPH per 100, 000 adult female population, adjusted for state economic productivity, welfare policies, demographic characteristics, firearm availability, and non-familial homicide rates. Results: A modest negative association between increased state EITC generosity and IPH rates was found. In the fully-adjusted models, a 10% increase in refundable state EITC (as percentage of federal) was associated with a reduction of 0.12 IPH events per 100, 000 female-years (95% CI:-0.23, -0.01). Conclusions: Increased state EITC generosity was associated with a small but significant reduction in IPH rates. The modest effects may relate to current EITC eligibility rules which typically preclude people who are married but separated from receiving benefits. Significance: Cash assistance to low-income families may be an important policy to prevent IPH, but the mechanisms through which cash transfers are meted out may affect their impact. Creating state EITCs, increasing their generosity, and changing eligibility rules for married individuals filing separately (as Massachusetts is exploring) may protect against IPH.